Relationship between reduced exposure to estrogen over a lifetime and bone mineral density in postmenopausal women (Journal of Health Sciences, 2018)
Introduction: The influence and interactions of various genetic, hormonal, environmental and nutritional factors and risks for decreased bone mineral density in older age are not yet clear. The aim of this study was to examine relationship between reduced exposure to estrogen over a lifetime (early age at menopause, shorter period between menarche and menopause) and bone mineral density in older women.Methods: A total of 60 women, aged 60-75 years were included and assigned to osteoporosis group (n=30), or control group with normal bone mineral density or osteopenia (n=30). The values ​​of bone mineral density were obtained by dual energy X-ray absorptiometry (DXA) at the lumbar spine (L2-L4) and proximal femur.Results: Women with osteoporosis entered the menopause at a younger age (43.03±3.18 years) compared to women without osteoporosis (51.93± 2.30 years) and the difference was statistically significant, p=0.0001. In addition, women with osteoporosis had shorter timespan between menarche and menopause (28.33±3.31 years), compared to women without osteoporosis (38.43±2.48 years), which was statistically significant, p=0.0001.Conclusion: Reduced exposure to estrogen over a lifetime because of early menopause, and shorter timespan between menarche and menopause may be associated with decreased bone mineral density and osteoporosis in postmenopausal women.